1B3u Pyrazine. Experimental Tests of the Theory of Radiationless Transitions. Issue 3 (1983) - Matsumoto, Y.; Spangler, L. H.; Pratt, D. W.
Abstract : Pyrazine (1, 4-diazabenzene) has played a central role in the development of the theory of radiationless transitions. In this paper, we will describe studies of the decay behavior and fluorescence quantum yield of the isolated molecule and several of its isotopically labelled derivatives following pulsed dye laser excitation of "single" rotational levels of the 1 B 3 u ( n π*) state in a seeded supersonic jet, both in the presence and absence of an external magnetic field. We shall demonstrate that pyrazine can be transformed from a "small" molecule to a "large" molecule by very small perturbations; e.g., by climbing up the rotational ladder of the first excited singlet state, by isotopic labeling, and/or by applying dc magnetic fields of the order of 100 G. Thus, the experiments provide important tests of the predictions of the theory for the first time. Specifically, we will show that, under "intermediate-case" conditions, (1) the fast component of the decay is indeed coherent in nature, (2) the coupled state is triplet in character (and, thus, that the process we are monitoring is intersystem crossing (ISC)), (3) nuclear spin is conserved in ISC, (4) rotations and small magnetic fields play an important role because of the angular momentum selection rules for ISC, and (5) the levels mixed by the magnetic field are most likely the fine-structure components of the different angular momentum levels of the mixed, singlet–triplet state. The relationship of these results to those of other workers in the field will also be discussed.